Literature Review: Faktor yang Berhubungan dengan Sindrom Burnout pada Perawat Rumah Sakit - Mawaddah, Dyah Wardana Harum; Mandagi, Ayik Mirayanti (Universitas Airlangga, 2024)
Background: Excellent service by hospitals is not far from the role of their workers, such as doctors, nurses, and other health workers and staff. Behind the hard work of health workers in providing services, they have a high risk of experiencing burnout syndrome. Research on burnout shows that the health profession ranks first with the most burnout, which is around 43%. Especially nurses who have an important role in patient recovery and safety. Not a few nurses experience fatigue due to their very heavy responsibilities. Therefore nurses have a great risk of suffering from burnout syndrome. Purpose: To examine more deeply the factors associated with the incidence of burnout syndrome in hospital nurses. Methods: This study is a systematic review with article searches used the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis. Article search used google scholar database. The inclusion criteria were articles published in national level journals, the year of publication of articles published in the last 5 years (2018-2023), research articles could be accessed in full (full text), and articles in Indonesian. Exclusion criteria in this study were the journal published in not more than 5 years, research outside the hospital, and full articles that could not be accessed. Results: The dominating factor in the incidence of burnout syndrome in nurses based on the seven articles reviewed stated that the workload carried by nurses was the trigger. Nurses had other responsibilities that must be carried out in addition to nursing care which was their obligation, so the workload became hard. Other factors driving burnout in nurses included length of service, gender, age, and marital status. Conclusion: The majority articles stated that workload was the dominant factor triggering burnout in hospital nurses. There were also other factors such as length of service, gender, age, and marital status.